Long-term methylphenidate intake in chronic fatigue syndrome. Issue 6 (1st November 2016) - Blockmans, Daniel; Persoons, Philippe
Abstract : Objective: Concentration disturbances are frequent in chronic fatigue syndrome (CFS). In a placebo-controlled double-blind crossover study, methylphenidate over 4 weeks was superior to placebo in the relief of fatigue and concentration disturbance. This observational study describes the effect of long-term methylphenidate intake on fatigue, concentration, and daily life activities, as reported by the patients themselves. Methods: A questionnaire was sent to all CFS patients who were prescribed methylphenidate at the general internal medicine department of a university hospital between August 2004 and February 2007, for possible improvement of concentration difficulties and fatigue. Results: Out of 194 consecutive patients, 149 (76.8%) sent the questionnaire back. At the time of the questionnaire, 65.3% had stopped the intake of methylphenidate, 34.7% still took it daily or occasionally. Among the patients who continued methylphenidate, 48% reported an at least 50% improvement of fatigue, and 62% reported an at least 50% improvement of concentration difficulties. This continued intake of methylphenidate resulted in more working hours in these patients. Side effects (agitation, palpitations, and dry mouth) were reported significantly more in patients who had stopped methylphenidate than in those who still took it. Conclusion: The long-term intake of methylphenidate by CFS patients with concentration difficulties has a positive effect in about one out of three patients.